A Biometric study on Penguin skin as an exterior wall insulation system utilizing agricultural waste - Bebelone, John Elmar R.; Juanga, Jean Marie V. (2020)
Global warming and climate change bring a new challenge to designers and scientists alike. With this rising problem, sustainability in building design is needed. Sustainability answers these problems in a lot of ways, of which is biomimicry. In this study, the proponent explored the application of penguin feathers as building envelope utilizing agricultural waste for thermal insulation. These agricultural wastes are abundant in tropical countries like the Philippines, namely, rice hull and waterlily. The study specifically aimed to describe the analogy on the biomimicry concept of the penguin skin layers and the potential materials to emulate the structure. It also aimed to determine the change in temperature (?T) of the interior and exterior simulation of the box chamber. Also, it aimed to compute for the thermal performance Beta (?) of the Penguin EWIS and compare it with other commercially available materials. Lastly, it aimed to determine the study?s application in an architectural project. The resulting data of the study was derived from 8 variables of which 3 are controlled and 5 are dependent. The resulting data showed that the treatment with plainly rice hull deemed the most effective in insulating followed by rice hull and waterlily mixture. The dependent variables deemed to be better alternatives than the controlled ones. Hence, the biomimetic EWIS proved effective. The study proved that biomimicry can not only be an alternative to sustainable building technology but also be the answer to rising problems of agricultural wastes in the country.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020